Legal Consequences for Parties Bound by Employment Agreements That Are Not in Accordance with Company Regulations At PT Banyuasin Nusantara Sejahtera - Ananda Hakikie; Joni Emirzon; Abdul Latif Mahfuz (Universitas Labuhanbatu, 2024)
Work agreements in a company must comply with company regulations but company regulations come into effect after being ratified by the Minister of Manpower or an appointed official. The formulation of the problem in this study is 1) What are the legal consequences for parties bound in a work agreement that are not in accordance with Company Regulations at PT Banyuasin Nusantara Sejahtera?; and 2) What is the legal settlement if a dispute arises due to a work agreement that is not in accordance with Company Regulations at PT Banyuasin Nusantara Sejahtera? The research method used is normative juridical research method. The data used in this research is secondary data. Based on the results of the study, it shows that 1) The legal consequences for parties bound by a work agreement that are not in accordance with Company Regulations at PT Banyuasin Nusantara Sejahtera are null and void by law and apply according to the provisions stipulated by. Legislation because the contents of the work agreement must not conflict with applicable company regulations and if there are conflicting provisions; and 2) Legal settlement if a dispute occurs due to a work agreement that is not in accordance with Company Regulations at PT Banyuasin Nusantara Sejahtera, namely Mediation, Conciliation and Arbitration